Programas de secagem para quatro madeiras tropicais - Lima, Maúcha Fernanda Mota de (2020)
Drying is an essential process in the industrialization of wood, since it leads to greater stability, durability, quality and added value to the final product. However, in order to conduct a properly drying, it is necessary to establish a program based on the specific wood characteristics. Although there are pre-established programs for tropical species, but they have been poorly evaluated. Thus, the objective was to elaborate and evaluate drying programs for tropical species based on drastic drying. Woods of Astronium lecointei, Dinizia excelsa, Hymenolobium heterocarpum and Qualea paraensis from the Jamari National Forest were used, determining their chemical, anatomical and physical properties. The drying potential and initial and final estimated temperatures were used to prepare the drying programs for each wood species. The programs were applied in a laboratory kiln with forced air circulation, and then the drying rates and defects of each wood species were evaluated. For Dinizia excels it was verified high content of extractives, and vessel diameter with reduced frequency, and obstructed, with heavy basic specific mass and low porosity. Astronium lecointei showed similar behavior to the previous wood species, differing with a high frequency of vessels, but totally obstructed by silos. Thus, low initial moisture content and reduced drying rates were observed for these woods. The woods of Qualea paraensis and Hymenolobium heterocarpum had similar characteristics, so we observed low contents of extractives, vessels with large diameter and low frequency, the specific mass was medium with high porosity. Thus, it resulted in high initial moisture contents, and higher drying rates, above 10% day-1 of green to PSF for these woods. Regarding the drying defects, in all wood species top and surface cracks were observed. It should be noted that the woods presented more than one type of warping, however the values were lower than the maximum limit established by NBR 14806. However, there was twisting for woods that presented irregular grain, being classified as defective. The collapse was observed in a slight degree for woods of Dinizia excelsa and Hymenolobium heterocarpum, with values below 0.5 mm. It is concluded that knowing the anatomical, physical and chemical characteristics may help to understand the behavior of woods during drying, since the movement of water inside the wood is related to its structure. Regarding the drying defects, the woods were classified as defective due to the high incidence of cracks and presence of twisting.